PySpark Cookbook : Over 60 recipes for implementing big data processing and analytics using Apache Spark and Python /: Over 60 recipes for implementing big data processing and analytics using Apache Spark and Python. (2018) - Drabas, Tomasz; Lee, Denny
No abstract available